2005
DOI: 10.1002/mrm.20603
|View full text |Cite
|
Sign up to set email alerts
|

Hemispherical gradient coils for magnetic resonance imaging

Abstract: Hemispherical gradient coils offer an open geometry that is well suited to imaging of the human brain. The windings of a hemispherical gradient coil are on average closer to the target region than those of a comparable cylindrical coil, and consequently hemispherical coils can produce higher efficiency at fixed inductance. The mathematical formalism needed for the design of hemispherical gradient coils is described here, including expressions relating the current distribution on the hemisphere to the magnetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0
1

Year Published

2007
2007
2010
2010

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 17 publications
0
18
0
1
Order By: Relevance
“…Liu and Petropoulos (71) described the design of spherical z-gradient coil using minimum inductance approach. Green et al (72) took the hemispherical gradient coil idea and adds a term where consider the total torque formed from a stream function (77). When this is not considered, the net torque makes its operation at high currents and fields problematic, although this inclusion of torque-balancing produces a considerable reduction of the performance of the transverse hemispherical coils, as is also the case for asymmetric, cylindrical coils.…”
Section: Torquementioning
confidence: 99%
“…Liu and Petropoulos (71) described the design of spherical z-gradient coil using minimum inductance approach. Green et al (72) took the hemispherical gradient coil idea and adds a term where consider the total torque formed from a stream function (77). When this is not considered, the net torque makes its operation at high currents and fields problematic, although this inclusion of torque-balancing produces a considerable reduction of the performance of the transverse hemispherical coils, as is also the case for asymmetric, cylindrical coils.…”
Section: Torquementioning
confidence: 99%
“…Myers and Roemer showed that cylindrical gradient coils with asymmetrically positioned regions of uniformity (ROU) have high efficiency and reasonable gradient field uniformity (8). There are many more examples of coil designs that deviate from cylindrical geometry; planar gradients for NMR microscopy (9) and ''open'' MRI systems (10), gradients with a hemispherical geometry for brain imaging (11,12), gradients with parabolic return paths to accommodate the shoulders (13), conical section surfaces linking the primary to the shield for short gradients (14), gradients with multiple regions of interest (ROI) (15) and MAMBA coils for simultaneous acquisition of images from different sample regions (16).…”
Section: Introductionmentioning
confidence: 99%
“…Another design method (11) represents current density on the primary coil by a finite series expansion, assuming the shield coil is much longer than the primary coil. Though most methods are typically used to design whole-body gradients, they have also been applied to small animal imaging and organ-specific imaging applications such as kidney and head (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29).…”
Section: Introductionmentioning
confidence: 99%
“…Designing a small-head gradient coil, in particular, requires advanced optimization techniques because of gradient performance tradeoffs forced by the need to take body shape, primarily the shoulders, into account. Various methods have been proposed: parabolic shoulder cutouts (20,21), gradients with an asymmetric center position (18-20, 23, 24, 27), a symmetric gradient (26,28), an edge gradient (26), and a hemispherical gradient (29). There have also been other head gradient design developments, such as the use of axial return paths (25,28).…”
Section: Introductionmentioning
confidence: 99%